ENHANCING TVET FOR A DIGITAL-READY WORKFORCE: A SYSTEMATIC LITERATURE REVIEW - Selvi Rajamanickam; Ridzwan Che’ Rus; Mohd Nazri Abdul Raji (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This study explores the integration of Industry 4.0 (IR 4.0) technologies into Technical and Vocational Education and Training (TVET) systems, aiming to cultivate a workforce prepared for digital challenges. With the rapid progression of technologies such as the Internet of Things (IoT), artificial intelligence (AI), big data, and robotics, there is a pressing need for TVET systems to evolve. This systematic literature review assesses how on-the-job training (OJT) enhanced with IR 4.0 technologies can advance TVET development. Despite the potential benefits, such as improved learning outcomes through the application of virtual reality (VR) and augmented reality (AR) in simulated training environments, and the customization of learning experiences through big data, there are significant challenges to address. The study follows a rigorous three-phase systematic review methodology. It begins with an identification process using key search terms across databases like Scopus and ERIC, leading to the selection of 281 articles. After screening and applying inclusion/exclusion criteria, 22 articles were finalized for full review. There is a disparity in access to these advanced technologies across different regions, potentially exacerbating existing inequalities in educational outcomes. This review aims to explore these issues comprehensively, offering a critical examination of the ways in which TVET can adapt to not only incorporate IR 4.0 technologies but also overcome the barriers to their successful implementation, thereby truly enhancing the capability of the workforce to meet the demands of a digital future.